PENGADAAN BAHAN BAKU DAN NILAI TAMBAH PISANG BOLEN DI BANDAR LAMPUNG - Lika Masesah; Ali Ibrahim Hasyim; Suriaty Situmorang (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2013)
This study aims to analyze the process of procurement of raw materials and value-added of banana bolen in Bandar Lampung. The study was conducted in Kedaton Jaga Baya II  District of Bandar Lampung in October-December 2011. The method used is the survey method. The number of respondents was 2 banana bolen home industries. Analysis methods used were Economic Order Quantity (EOQ) and Hayami value-added model. The averages of raw bananas used was 3,000 comb/month by CV Mayang Sari and 520 comb/month by Harum Sari. Value-added of banana bolen of CV Mayang Sari was Rp3.937,60 per one banana bolen box and value-added of banana Bolen Harum Sari was Rp23.269,02 per one banana bolenbox.Key words: industry, process, banana bolen, procurement of raw materials, Hayami model